Neonicotinoid pesticides: evidence of developmental neurotoxicity from regulatory rodent studies - Sass, Jennifer Beth; Donley, Nathan; Freese, William (Frontiers in Toxicology, 2024)
Neonicotinoids are the most widely used class of insecticides in the United States (U.S.). and the world. Consistent with their high use and persistence, neonicotinoids are often found contaminating drinking water and food. They are also detected in human urine, breast milk, amniotic and cerebrospinal fluids, as well as the brains of treated rodents. Neonicotinoids were once thought to pose little neurotoxic risk to humans, but a growing body of research challenges that assumption. In this study we provide the first comprehensive assessment of unpublished rodent developmental neurotoxicity (DNT) studies on five neonicotinoids that were submitted to the U.S. Environmental Protection Agency (EPA) by neonicotinoid manufacturers. Groups of female rats were administered three different doses of a neonicotinoid during pregnancy and lactation, and their offspring subjected to various neurological tests and brain measurements. We identified nicotine-like effects such as reduced brain size, indicative of neuronal cell loss. Statistically significant shrinkage of brain tissue was observed in high-dose offspring for five neonicotinoids: acetamiprid, clothianidin, imidacloprid, thiacloprid, and thiamethoxam. Two brain regions reduced in the rodent studies–the corpus callosum and caudate-putamen–tend to be smaller in people diagnosed with attention-deficit hyperactivity disorder (ADHD), and in children of mothers who smoked during pregnancy, suggesting a possible link between perinatal neonicotinoid exposure and ADHD. A decreased auditory startle reflex was reported for acetamiprid at all doses and was statistically significant in the mid- and high-dose offspring, and for clothianidin in juvenile high-dose females. No mid- or low-dose brain morphometric data were submitted for acetamiprid, imidacloprid, or thiacloprid. Thiamethoxam mid- and low-dose brain morphometric data were provided to EPA upon request. Only partial mid-dose brain morphometry data were submitted for clothianidin, but no low-dose data. Yet despite this lack of data, EPA concluded that only the high-dose brain morphometric effects were treatment-related–setting the mid-dose as the study’s No Observed Adverse Effect Level (NOAEL) or failing to find a definitive NOAEL for acetamiprid, clothianidin, imidacloprid, thiacloprid and thiamethoxam. We found numerous deficiencies in EPA’s regulatory oversight and data analyses. EPA dismissed statistically significant adverse effects, accepted substandard DNT studies despite lack of valid positive control data, and allowed neonicotinoid registrants to unduly influence agency decision-making. We conclude that perinatal exposure to neonicotinoids and their metabolites induces adverse, nicotine-like neurotoxic effects in rodent bioassays, and that the exposure limits set by EPA for human exposure are either not protective or not supported by available neurotoxicity data. We propose regulatory changes to empower EPA to better protect public health from developmental neurotoxins like neonicotinoids.